Pictolysin-III, a Hemorrhagic Type-III Metalloproteinase Isolated from Bothrops pictus (Serpentes: Viperidae) Venom, Reduces Mitochondrial Respiration and Induces Cytokine Secretion in Epithelial and Stromal Cell Lines - Dan E. Vivas-Ruiz; Paola C. Rosas; Álex Proleón; Daniel Torrejón; Fanny Lazo; Ana Belén Tenorio-Ricca; Francisco Guajardo; Cristopher Almarza; Víctor Andrades; Jessica Astorga; Daniel Oropesa; Jorge Toledo; et al. (2023)
From the venom of the Bothrops pictus snake, an endemic species from Peru, we recently have described toxins that inhibited platelet aggregation and cancer cell migration. In this work, we characterize a novel P-III class snake venom metalloproteinase, called pictolysin-III (Pic-III). It is a 62 kDa proteinase that hydrolyzes dimethyl casein, azocasein, gelatin, fibrinogen, and fibrin. The cations Mg2+ and Ca2+ enhanced its enzymatic activity, whereas Zn2+ inhibited it. In addition, EDTA and marimastat were also effective inhibitors. The amino acid sequence deduced from cDNA shows a multidomain structure that includes a proprotein, metalloproteinase, disintegrin-like, and cysteine-rich domains. Additionally, Pic-III reduces the convulxin- and thrombin-stimulated platelet aggregation and in vivo, it has hemorrhagic activity (DHM = 0.3 µg). In epithelial cell lines (MDA-MB-231 and Caco-2) and RMF-621 fibroblast, it triggers morphological changes that are accompanied by a decrease in mitochondrial respiration, glycolysis, and ATP levels, and an increase in NAD(P)H, mitochondrial ROS, and cytokine secretion. Moreover, Pic-III sensitizes to the cytotoxic BH3 mimetic drug ABT-199 (Venetoclax) in MDA-MB-231 cells. To our knowledge, Pic-III is the first SVMP reported with action on mitochondrial bioenergetics and may offer novel opportunities for promising lead compounds that inhibit platelet aggregation or ECM-cancer-cell interactions.